Ustroje kościołów ewangelicko‑reformowanych w Rzeczypospolitej Obojga Narodów na przełomie XVI i XVII wieku - Bem, Kazimierz (Odrodzenie i Reformacja w Polsce, 2013)
The polity of the Reformed Church in the Commonwealth of Two Nations from the mid 16th to the mid 17th centuries The article looks at the polity of the three Reformed Churches in the Commonwealth of the Two Nations in the context of the Second Reformation. The author argues that the three churches began with initially very different ecclesiastical polities. The Czech Brethren Church (Jednota Braci Czeskich) in Greater Poland had an Episcopal structure with the bishops (called “seniors”) making all the decisions for the church. The Lesser Polish Brethren (Jednota Małopolska) began as a highly decentralized church, resembling a de facto congregationalism. Finally, the Lithuanian Brethren (Jednota Litewska) was from the onset a church with a classical Presbyterian polity. With the passage of time and due to many factors all three churches began to resemble each other more and more and moving towards the Presbyterian polity. It was embraced by the Lesser Poland Reformed from the 1590s onwards, and the Brethren Church after 1608. This process – paralleled by a liturgical and organizational uniformity – culminated in the Synod of Włodawa (1634) when the Reformed of all three provinces settled on a Presbyterian polity for all three churches, with minor local variations. While all the churches retained the functions of superintendents or seniors, the mere fact of their existence or competence is not enough to suggest an Episcopal polity for any of three churches.